The Copper Babysitter Robot, a Childcare Monitoring System From the First Year of Age - Bastidas Alva, Ruth Alejandra (2024)
This research work presents the design of a mobile robot that monitors the care and integrity of children from the first year of life. The monitoring is done with a surveillance system that uses artificial vision to identify the environment and with help of the SLAM system, the robot can move without any difficulty since the robot itself will be able to map and locate in the environment. The presence sensors also contribute to the robot's displacement, as they work together with the SLAM system to measure the robot's distance from objects to avoid collisions. The robot will have two drives, one manual and the other automatic; the choice will be made through an app interface with which the robot's movement can be controlled; this application can also display the webcam video in real time. In addition to this, there is an alert system in which when the robot detects risk or danger to the child, it emits an alarm and makes a call to the caregiver or parent. This design presents a stable and pleasant structure for the child, an intuitive mechanism for the user and all the suitable components for proper operation. The results of the project will be used to create more complex monitoring and alerting systems.